GENERAL THEORETICAL ISSUES OF ORGANIZING CHORAL CIRCLES IN SECONDARY SCHOOLS (Web of Teachers: Inderscience Research, 2024)
In this article, the general theoretical issues of organizing choral clubs in secondary schools are highlighted, in which cultural and art institutions, choral clubs organized outside of school and classroom are responsible for forming the musical ideology of students and young people. It was explained in order to inculcate them in their consciousness.